Технічна реалізація системи автоматичного управління режимом низьковольтної розподільчої електричної мережі з відновлюваними джерелами енергії - Солдатенко, В. П.; Зінзура, В. В.; Плєшков, С. П.; Гарасьова, Н. Ю.; Величко, Т. В.; Зинзура, В. В.; Плешков, С. П.; Гарасева, Н. Ю.; Soldatenko, V.; Zinzura, V.; Plieshkov, S.; Harasova, N.; et al. (ЦНТУ, 2019)
Здійснено розробку мікроконтролерного блоку автоматичного управління режимом генерації активної потужності установок з відновлюваними джерелами енергії, що працюють в складі комбінованої електроенергетичної системи. Розроблено структурну та принципові схеми даного блоку, які було використано для створення макету пристрою. Проведено експериментальні дослідження розробленої мікроконтролерної системи автоматичного управління, результати яких підтвердили її працездатність. Произведена разработка микроконтроллерного блока автоматического управления режимом генерации активной мощности установок с возобновляемыми источниками энергии, работающих в составе комбинированной электроэнергетической системы. Разработана структурная и принципиальные схемы данного блока, которые были использованы для создания макета устройства. Проведены экспериментальные исследования разработанной микроконтроллерной системы автоматического управления, результаты которых подтвердили ее работоспособность. The purpose of the study is to develop a microprocessor-based automatic control system, the application of which will provide the highest possible level of generation of active power to the units of RES, which are part of the EEC, subject to the observance of the normally acceptable values of the established voltage deviation at the point of connection of consumers to the electrical distribution network. A block diagram of a microprocessor-based automatic control system for generating the active power of renewable energy sources operating within a combined power system using a modern element base has been developed. Structural and schematic diagrams of the microprocessor-based automatic control system were developed, based on an algorithm for determining the optimal control vector based on the solutions of the multicriteria optimization problem. The developed laboratory stand for the experimental study of the quality of work of the automatic control system of generation of active power of renewable energy sources working in the combined electric power system allowed to perform the experimental researches of the microprocessor automatic control system. Experimental studies were conducted to test the performance of the developed microprocessor-based system for automatic control of the level of active power generation, as well as to determine its efficiency. Comparison of the results of the experimental studies with the data of computer simulation and the results of statistical data showed the correctness of the theoretical studies and the efficiency of the developed system of automatic control of the generation of active power of renewable energy sources operating in the combined electricity system.
Техническая реализация системы автоматического управления режимом низковольтной распределительной электрической сети с возобновляемыми источниками энергии
Technical Implementation of the Automatic Control System of the Low-voltage Distribution Network with Renewable Energy Sources
Keywords: система автоматичного управління; відновлювані джерела енергії; система автоматического управления; возобновляемые источники энергии; automatic control system; renewable energy sources